The effect of interleukin-6 and procalcitonin level on the development of oral manifestation in hospitalized COVID-19 patients - Enas Ahmed Elgendy; Ahmed Mohammad Ali Elgendy; Marwa Sabry; Mohamed Kamal Salama; Tamer Aboshady (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effect of interleukin-6 and procalcitonin levels in plasma on the development of oral manifestation in patients of coronavirus disease-2019. Methods: The case-control study was conducted from January to September 2021 at Kafrelsheikh University Hospital, Egypt, and comprised severe coronavirus disease. One hundred patients of either gender aged 30-60 years were included. The patients were divided into two equal groups, with group I having patients with oral manifestations, and group II had those without any oral symptoms. Plasma samples from both the groups were used to determine serum interleukin-6 and procalcitonin levels using electrochemiluminescence immunoassay. Data was analysed using SPSS 20. Result: Of the 100 patients, 50(50%) were in each of the two groups. Group I had 29(58%) males and 21(42%) females with overall mean age 44.83±6.12 years. Group II had 26(52%) males and 24(48%) females with overall mean age of 43.68±4.62 years. Interleukin 6 was significantly high in group I than in group II (p<0.05), while there was no significant difference between the groups for procalcitonin level (p>0.05). Conclusion: Interleukin-6 level could play an important role in the development of oral manifestation in coronavirus disease-2019 patients. Keyword: Interleukin, Procalcitonin, Ageusia, COVID-19, Gingivitis, Candidiasis, Mucous membrane, Immunoassay.